Hyperuricemia Associated with Low Skeletal Muscle in the Middle-Aged and Elderly Population in China - Chen, Lingyan; Wu, Li; Li, Qian; Hu, Yu; Ma, Hui; Lin, Huandong; Gao, Xin (Experimental and Clinical Endocrinology & Diabetes, 2022)
Background Previous studies have presented inconsistent results on the relationship between serum uric acid and skeletal muscle mass (SMM). We aimed to explore whether a higher serum uric acid level was associated with low SMM in the Chinese population.Methods We performed a cross-sectional analysis of 6595 subjects aged 45 years or older. They were tested for fasting blood glucose, total cholesterol, triglycerides, high-density lipoprotein-cholesterol, low-density lipoprotein-cholesterol, uric acid, blood urea nitrogen, creatinine, and estimated glomerular filtration rate. SMM was accessed by dual-energy x-ray absorptiometry using two approaches: weight-adjusted appendicular skeletal muscle mass (ASM)% and ASM/BMI (body mass index (kg/m2)). Low SMM was defined as a cut-off point of ASM/BMI<0.789 for men and<0.512 for women.Results Compared with their normal group, patients with hyperuricemia had lower ASM% (29.33±2.33 vs 30.03±2.34 for males and 24.71±1.99 vs 25.19±2.07 for females, P<0.01) and ASM/BMI (0.83±0.10 vs 0.85±0.10 for male and 0.60±0.07 vs 0.62±0.07 for female), with a higher prevalence of the associated low SMM in both sexes (35.2 vs 26.5% for male and 10.5 vs 5.9% for female, P<0.01). Pearson analysis showed that ASM% and ASM/BMI were negatively correlated with SUA (male: ASM/BMI, r=−0.097, ASM%, r=−0.146; female: ASM/BMI, r=−0.151, ASM%, r=−0.157; all P<0.001). Logistic regression analysis showed a positive association of hyperuricemia with adjusted risk of low SMM association.Conclusions In a middle-aged and elderly Chinese population, hyperuricemia is independently and positively associated with low SMM and can vary by age and gender.
Keywords: uric acid; skeletal muscle mass; middle-aged and elderly community people; sarcopenia